True crime : a memoir [large type] - Cornwell, Patricia Daniels (Grand Central Large Print, 2026)
Patricia Cornwell is best known for her international bestselling thriller series about forensic pathologist Dr. Kay Scarpetta. Every story comes from somewhere, and Scarpetta's began when Patricia Cornwell embedded herself in a morgue. In this achingly honest memoir, Cornwell excavates her own life, detailing her traumatic childhood being raised by neglectful parents, her father abandoning the young family on Christmas day, her mother being institutionalized twice, an abusive foster family, and developing a parental relationship with evangelist Billy Graham's wife Ruth. Cornwell depicts a harrowing hospitalization and near-death car accident. She unflinchingly shares overcoming obstacles that later gave her the ambition to become an award-winning police reporter. From there it was research in a medical examiner's office that would turn into a full-time job. She would become a forensic expert and worldwide publishing phenomenon. Cornwell leaves no stone unturned in this deeply candid account of her life, offering inspiring insight into what made her into the international sensation she is today.